METHOD DEVELOPMENT AND VALIDATION OF PHOTOMETRIC DETERMINATION OF IRON IN HEMOSTATIC TOOL - Yu. N. Barsukova; O. A. Melnikova; M. Yu. Melnikov (Разработка и регистрация лекарственных средств, 2019)
The article presents data on the development of a technique of photometric determination of ferric chloride (III) as a hemostatic tool, through the formation of salicylates iron. The developed method was validated for following validation characteristics: specificity, linearity, accuracy. The results of the study the main validation characteristics of the method meet the acceptance criteria. The technique is intended for definition of iron in the painted solutions of medicines in the range of 0,04-0,07 g/ml. Relative error of measurement of 0,83%.